1998
DOI: 10.1142/s0192415x98000300
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cortex Participation in the Physiological Mechanisms of Acupuncture Stimulation: A Study by Auditory Endogenous Potentials (P300)

Abstract: Although acupuncture has traditionally used the acupoints formula to treat diseases, the physiological mechanisms involved and the effectiveness of therapy remain unclear. This study investigated the physiological mechanism(s) and response to acupuncture stimulation using the acupoints formula. Scalp-recorded potentials P300 were evoked by auditory stimulation of non-target and target in 13 normal adult volunteers. Latencies and amplitudes were measured. Three assessments were performed in each subject over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although acupuncture at the right and the left GB34 was shown to have different effects, this study was conducted on healthy participants; therefore, replication studies are needed with right versus left GB34 acupuncture on patients with motor problems (e.g., patients with Parkinson's disease) [7]. Also, replication studies with different scanning procedures (e.g., the resting state fMRI acupuncture procedure [58] instead of the present block design) or with different neuroimaging techniques, such as EEG [59] or MEG [60], are warranted. Moreover, if the question of whether the difference between the effects of right side versus left side acupuncture stimulation is a general issue that needs to be considered in acupuncture treatment is to be answered, replication studies with acupuncture points other than GB34, for instance, with Hegu (LI4), Zusanli (ST36), and Taichong (LV3), are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although acupuncture at the right and the left GB34 was shown to have different effects, this study was conducted on healthy participants; therefore, replication studies are needed with right versus left GB34 acupuncture on patients with motor problems (e.g., patients with Parkinson's disease) [7]. Also, replication studies with different scanning procedures (e.g., the resting state fMRI acupuncture procedure [58] instead of the present block design) or with different neuroimaging techniques, such as EEG [59] or MEG [60], are warranted. Moreover, if the question of whether the difference between the effects of right side versus left side acupuncture stimulation is a general issue that needs to be considered in acupuncture treatment is to be answered, replication studies with acupuncture points other than GB34, for instance, with Hegu (LI4), Zusanli (ST36), and Taichong (LV3), are needed.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that acupuncture doesn't change the monosynaptic reflex at the brainstem and spinal level. Indeed, utilizing auditory endogenous potentials (P300), we elucidated that cerebral cortex is the major location where acupuncture interferes sensory processing [57].…”
Section: The Role Of Central Nervous System (Cns) On Acupuncture Treamentioning
confidence: 99%
“…It is more acceptable than traditional acupuncture by patients [ 5 ]. However, the physiological mechanisms are still unclear [ 6 ]. The mode of stimulation or location of acupuncture points is specific to producing different physiological effects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%